Symbolic Claims in Indonesia's Aid to Pacific Island Countries - Mooy, Jeniar Nelsus (Institute of International Studies, 2024)
Within the discourse of aid in the global South, where a developing country provides foreign aid to another developing country, emerged discussions on the extent to which the symbolic claims presented by the donor to the public (e.g. the aid as being driven by the donor’s sense of mutual respect, horizontality, inclusivity, and solidarity with the recipient) reflect the real motivations behind the aid. Using the case study of Indonesia’s aid to Pacific Island countries (PIC), this research assesses the relations between symbolic claims and critical aid drivers. This research uses a qualitative method and secondary data, which rely mainly on official statements and publications of the Indonesian government. This research found that whilst symbolic claims in Indonesia's aid narratives could strengthen the sense of Southern solidarity and identity with PIC – which is in line with the spirit of South-South empowerment that Indonesia has been championing since the Asia-Africa Conference in 1955, these claims are used mainly to obscure Indonesia’s internal political-security motive. The symbolic claims mask the critical political driver of the aid, which is closely related to Indonesia's interest in maintaining its sovereignty over West Papua province and influencing the stance of PIC about this issue.Keywords: aid; Global South; symbolic claims; solidarity; Indonesia-PIC relations